Blood Meals With Active and Heat-Inactivated Serum Modifies the Gene Expression and Microbiome of Aedes albopictus - Calle-Tobón, Arley; Holguin-Rocha, Andres F.; Moore, Celois; Rippee-Brooks, Meagan; Rozo-Lopez, Paula; Harrod, Jania; Fatehi, Soheila; Rua-Uribe, Guillermo L.; Park, Yoonseong; Londoño-Rentería, Berlin (Frontiers in Microbiology, 2021)
The Asian “tiger mosquito” Aedes albopictus is currently the most widely distributed disease-transmitting mosquito in the world. Its geographical expansion has also allowed the expansion of multiple arboviruses like dengue, Zika, and chikungunya, to higher latitudes. Due to the enormous risk to global public health caused by mosquitoes species vectors of human disease, and the challenges in slowing their expansion, it is necessary to develop new and environmentally friendly vector control strategies. Among these, host-associated microbiome-based strategies have emerged as promising options. In this study, we performed an RNA-seq analysis on dissected abdomens of Ae. albopictus females from Manhattan, KS, United States fed with sugar and human blood containing either normal or heat-inactivated serum, to evaluate the effect of heat inactivation on gene expression, the bacteriome transcripts and the RNA virome of this mosquito species. Our results showed at least 600 genes with modified expression profile when mosquitoes were fed with normal vs. heat-inactivated-containing blood. These genes were mainly involved in immunity, oxidative stress, lipid metabolism, and oogenesis. Also, we observed bacteriome changes with an increase in transcripts of Actinobacteria, Rhodospirillaceae, and Anaplasmataceae at 6 h post-feeding. We also found that feeding with normal blood seems to particularly influence Wolbachia metabolism, demonstrated by a significant increase in transcripts of this bacteria in mosquitoes fed with blood containing normal serum. However, no differences were observed in the virome core of this mosquito population. These results suggest that heat and further inactivation of complement proteins in human serum may have profound effect on mosquito and microbiome metabolism, which could influence interpretation of the pathogen-host interaction findings when using this type of reagents specially when measuring the effect of Wolbachia in vector competence.